(untitled) (International Journal of Engineering and Computer Science, 2016)
The prominence of the digital image processing is growing in the field of security, as now s days the transfer of images from one entity to another entity using internet as source of medium is increased. The digital image transmission has advanced applications in the field of security such as security related the confidentiality of medical databases, preventing leakages from the military databases, privacy protection the enterprise related documents and online document storage systems. Although lot of research has been done on secure image transmission but still it too has some unresolved issues such as leakages while transmissions and loss of the confidentiality is another drawback. An innovative approach is implemented in this paper and the main idea of the proposed work is create meaningful secret fragment mosaic image system and the important implementation in the proposed work is the secret fragment mosaic image size is same as that of preselected target image which gives scope to provide more payload capacity. The generation of the mosaic image is the resultant of the block fragments of the selected secret image and the mosaic image in the process is looks alike of the target image which is used as the source to hide the secret image by successfully transforming the color characteristics of the secret image similar to the blocks of the target image. Finally the simulation results show the performance in terms of presenting the meaningful secure image transmission technique for the lossless recovery and the necessary data is embedded into mosaic image for the recovery of the securely transmitted secret image.